A macromolecular cyclometalated gold(iii) amphiphile displays long-lived emissive excited state in water: self-assembly and in vitro photo-toxicity. Issue 90 (24th October 2016) - Wang, Feng; Lan, Minhuan; To, Wai-Pong; Li, Kai; Lok, Chun-Nam; Wang, Pengfei; Che, Chi-Ming
Abstract : A cyclometalated gold(iii ) amphiphile self-assembles into nano-sized micelles in water, displaying a long-lived emissive excited state and in vitro photo-toxicity. Abstract : We report an amphiphilic macromolecule containing a cyclometalated gold(iii ) complex that self-assembles into nano-sized micelles and also displays a long-lived emissive triplet excited state with a lifetime of 84 μs in degassed water. This amphiphilic Au III complex exhibits good biocompatibility and activity towards in vitro photo-toxicity, as well as enhanced permeability and retention effects in vivo .